1995
DOI: 10.1111/j.1748-1716.1995.tb09959.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of 2‐deoxyglucose and immobilization on secretion and synthesis rate of catecholamines in the adrenal gland: a microdialysis study in conscious rats

Abstract: Using microdialysis, extracellular 3,4-dihydroxyphenylalanine (DOPA), noradrenaline (NA) and adrenaline (AD) concentrations in the adrenal gland were monitored in conscious rats during and after 60 min of immobilization (IMM) as well as after injection of 500 mg kg(-1) 2-deoxyglucose (2-DG). IMM produced a rapid and transient increase in secretion of AD (20-fold), NA (13-fold) and DOPA (3.6-fold). This was accompanied by an increase in blood pressure (+18 mmHG) and heart rate (+146 b.p.m.). Repeated exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…4). As reported by others (Kuzmin et al 1995; Vollmer et al 1997; Morrison & Cao, 2000), we also found that 2‐DG had no significant effect on the NA content of normoxic and CIH adrenal medullae.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4). As reported by others (Kuzmin et al 1995; Vollmer et al 1997; Morrison & Cao, 2000), we also found that 2‐DG had no significant effect on the NA content of normoxic and CIH adrenal medullae.…”
Section: Resultssupporting
confidence: 88%
“…Since activation of nicotinic cholinergic receptors is critical for evoking neurally mediated CA secretion from the adrenal medulla, we hypothesized that CIH downregulates neurogenic mediation of CA secretion. To test this possibility, we assessed the effect of systemic administration of 2‐deoxyglucose (2‐DG), which selectively depletes ADR from the adrenal medulla by activating 2‐DG‐sensitive sympathetic fibres (Kuzmin et al 1995; Vollmer et al 1997; Morrison & Cao, 2000). In control rats, 2‐DG reduced adrenal ADR from 42 ± 0.5 to 9 ± 1.2 nmol per adrenal medulla (78% depletion; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glucoprivation is a potent stimulus for adrenal medullary secretion, which could potentially alter cardiovascular function and lead to changes in Fos expression in these cardiovascular areas. However, expression of Fos in TH-ir neurons after 2DG administration is not secondary to changes in cardiovascular parameters induced by glucoprivation, since 2DG does not alter blood pressure (22). In addition, 2DG-induced expression of Fos in TH-ir neurons is not altered by adrenal denervation, which completely blocks adrenal medullary secretion (7).…”
Section: Discussionmentioning
confidence: 92%
“…elicited a relatively selective increase in dialysate levels of EPI, while levels of NE remained constant. EPI/NE peaked at approximately 10.0 one hour after injection of 2-deoxy-D-glucose (Kuzmin et al, 1995). In an earlier study that combined adrenal medullary microdialysis and measurement of circulating catecholamines, Kuzmin et al (1990) reported that plasma NE from the adrenal medulla of laboratory rats increased from 9% under basal conditions to 50% during hemorrhage.…”
Section: Stressmentioning
confidence: 96%
“…Using microdialysis of the adrenal medulla of laboratory rats, Kuzmin et al (1995) studied the effects on catecholamine secretion of acute immobilization stress for 60 min. Adrenal medullary dialysate was collected before, during and after immobilization and later analyzed for content of NE and EPI.…”
Section: Stressmentioning
confidence: 99%